Oxytocic and Abortifacient Activities of Xylopia Aethiopica Ethanol Fruit Extract on Female Wistar Rats - Nwafor, Amuchechukwu Veronica; Ohanme, Eugene Ohams; Ofonakara, Uzochukwu; Eze, Clementina Nkiru; Okoroafor, Francis Chigozie; Iwe, Chukwujioke Bobbie; Uchenna, Onuchukwu Victor; Onwe, Abraham Bong; Orofuke, Grace Ngozi; Ghasi, Samuel (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Pregnancy describes the period of fetal development in the uterus until delivery. Pregnancy, labour and puerperium present challenges that encourage use of medications to relieve symptoms, terminate pregnancy and prevent primary postpartum haemorrhage. Some pregnant women still rely on herbal remedies for treatment of pregnancy related problems. X. aethiopica is a natural spice used in preparing soup for women after delivery to prevent primary postpartum haemorrhage. Objective: To investigate the oxytocic effects of ethanol fruit extract of Xylopia aethiopica (X. aethiopica). Methods: This experimental study was done on Sixty six adult wistar rats comprising of 12 males for mating and 44 females that weighed 150–180g were used in this study. Acute toxicity test, qualitative phytochemical analysis, abortifacient and oxytocic studies were all done. The Median LD50 was established to be 1703 mg/kg in rats. Results: The phytochemical analytes were found to be Flavonoids, phenols, cardiac glycosides and steroids. There was dose dependent decrease in body weight of the animals treated with X. aethiopica. The extract did not have oxytocic effect on postpartum uterus like oxytocin. It rather caused relaxation of the uterus. Conclusion: Ethanol fruit extract of X. aethiopica did not exert oxytocic effect on female wistar rats. It is, therefore, not recommended in the prevention of primary postpartum haemorrhage. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 268-274